English Writing Training in Grade VII of Kartika Junior High School, Pematangsiantar - Ika Purnama Sari; Harly Okprana; Iin Parlina; Rizky Khairunnisa Sormin; Riki Winanjaya; Rizki Alfadilah Nasution; Asmarani Nasution (Salus Publica: Journal of Community Service, 2025)
Kartika 1-4 Private Junior High School is a private junior high school located in Pematangsiantar City, specifically at Jalan Kartini No. 8, West Siantar District. Improving English language skills for seventh-grade students is an urgent need, making English language training crucial for educational practitioners at the school. This training can help students. The community service team's interest in the existing problem prompted them to organize an English training program, specifically writing skills. This shows that the team has a strong motivation to overcome the problem, especially writing skills in English. This training is designed to improve writing skills, which are important in various contexts such as academic, professional, or global communication. The focus on writing skills indicates a specific need that the community service team wants to meet. This training emphasizes the ability to express ideas and thoughts clearly and effectively through writing, not just copying words or sentences. The purpose of the training that has been implemented is to improve students' ability in writing in English, so that they can express ideas and information more effectively and clearly, especially when they want to write a sentence and form a paragraph correctly. The Community Service Activity was held for 32 seventh-grade students of Kartika Middle School located in Pematangsiantar. Students were enthusiastic about participating in this training activity. In addition, the seventh-grade students of Kartika Middle School also have more confidence in writing.